PENGARUH RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO AKTIVITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN INDUSTRI FARMASI TBK TAHUN 2019-2021 - Nur Kiatin; Fatimah Riswati (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aimed to examine the connection between liquidity ratios, solvency ratios, and activity ratios and financial output. Quantitative associative methods are used in this kind of study. All pharmaceutical businesses operating between 2019 and 2021 made up the sample for this analysis. Ten businesses were chosen using a purposive selection technique to make up the sample. Financial statements were employed as a supplementary source of information for the data gathering method. Analysis of data by use of computer statistical methods, namely regression analysis in SPSS. Analysis of the data using the t-test reveals a positive and substantial influence of the liquidity ratio on financial performance, a negative and insignificant effect of the solvency ratio, and no effect of the activity ratio. However, it is known that the liquidity ratio, solvency ratio, and activity ratio all have a considerable positive influence on financial performance at the same time.